Endothelial cell metabolism: A novel player in atherosclerosis? Basic principles and therapeutic opportunities. (October 2016) - Pircher, Andreas; Treps, Lucas; Bodrug, Natalia; Carmeliet, Peter
Abstract: Atherosclerosis is a leading cause of morbidity and mortality in Western society. Despite improved insight into disease pathogenesis and therapeutic options, additional treatment strategies are required. Emerging evidence highlights the relevance of endothelial cell (EC) metabolism for angiogenesis, and indicates that EC metabolism is perturbed when ECs become dysfunctional to promote atherogenesis. In this review, we overview the latest insights on EC metabolism and discuss current knowledge on how atherosclerosis deregulates EC metabolism, and how maladaptation of deregulated EC metabolism can contribute to atherosclerosis progression. We will also highlight possible therapeutic avenues, based on targeting EC metabolism. Highlights: Endothelial cell (EC) dysfunction contributes to atherosclerosis. EC metabolism determines vessel formation and EC homeostasis. EC metabolism is perturbed in atherosclerosis. Targeting EC metabolism offers new therapeutic options.